HUBUNGAN ANTARA KEHARMONISAN KELUARGA DAN MOTIVASI BELAJAR SISWA - indah, kartika sari; ., zikra; ., yusri (Konselor, 2013)
students motivation to learns influence by input and output students like family. The parents need to create harmony family such as sakinah, mawaddah, warrahmah family. The fact, often fight in the family because theirÂ  parents carelless to their children. Purpose of the research to the test about correlation harmony family and students motivation to learn. This method quantitative with kind of descriptive correlational. The reserchers found about harmony students family are enough, studens motivation to learn are enough and there are significant correlation between harmony family and students motivation to learn Keyword: Harmony family, Motivation to learn